The potential of genetically modified food crops to improve human nutrition in developing countries - Bouis, Howarth E. (Informa UK Limited, 2007)
Because of poor dietary quality and consequent widespread micronutrient malnutrition in low income countries, children and their mothers, who have higher requirements for vitamins and minerals due to rapid growth and reproduction respectively, have higher mortality, become sick more often, have their cognitive abilities compromised for a lifetime, and are less productive members of the workforce. Their quality of life and aggregate economic growth are unnecessarily compromised. One way that biotechnology can help to improve the nutrition and health of consumers in developing countries is by increasing the vitamin and mineral content and their bioavailability in staple foods.